2015
DOI: 10.1007/s11002-015-9355-0
|View full text |Cite
|
Sign up to set email alerts
|

The case of wine: understanding Chinese gift-giving behavior

Abstract: This study develops our understanding of consumption in China in a giftgiving context and highlights the boundary conditions under which country of origin effects impact wine gift-giving behavior. Using the Theory of Planned Behavior (TPB) as the core premise and borrowing from the embeddedness literature within network theory, we gauge unique insights into Chinese gift-giving behavior. Using survey results from 617 Chinese consumers, product image and gift packaging had significant moderating effects on relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 69 publications
3
50
0
1
Order By: Relevance
“…According to previous studies, 'origin' is among the most important wine attributes (e.g. Defrancesco et al, 2012;Jaeger et al, 2013;Mann et al, 2012;Yang and Paladino, 2015). Also in the present study, the choice of white wine was strongly influenced by the country of origin.…”
Section: Country Of Originsupporting
confidence: 56%
See 1 more Smart Citation
“…According to previous studies, 'origin' is among the most important wine attributes (e.g. Defrancesco et al, 2012;Jaeger et al, 2013;Mann et al, 2012;Yang and Paladino, 2015). Also in the present study, the choice of white wine was strongly influenced by the country of origin.…”
Section: Country Of Originsupporting
confidence: 56%
“…grape variety, micro-climatic conditions (like terroir, weather), and the wine-makers work in the cellar. When purchasing wine in grocery stores, it is often difficult for consumers to judge on wine quality and taste (Lockshin et al, 2006), which is why consumers mostly base their wine choice on extrinsic product attributes such as grape variety (Gustafson et al, 2016), origin (Defrancesco et al, 2012;Jaeger et al, 2013;Yang and Paladino, 2015), price (Panzone, 2014), brand and label design (Drennan et al, 2015).…”
Section: State Of the Art And Hypothesesmentioning
confidence: 99%
“…Besides wines from Bordeaux, Chinese consumers are more inclined to go for excellent wines from other wine regions of the world and getting more information from wine courses and websites (Masset et al, 2016). Enhanced customers' knowledge, product familiarity and emotional attachments to a specific wine region could contribute to the ethnocentrism of wine (Yang and Paladino, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have found that Chinese consumers rely more on extrinsic clues when they select wine due to their lack of wine knowledge (H. Liu & McCarthy, 2017). Many studies have revealed that the country of origin (COO) plays an important role when Chinese consumers purchase wine (Balestrini & Gamble, 2006;Camillo, 2012;Hu et al, 2008;Yang & Paladino, 2015;Yu et al, 2009). Drinking wine is considered a symbol of an elegant Western lifestyle, so wine from the Old World, particularly from France, is popular in China (Xu et al, 2014).…”
Section: Attributes Of Wine Selection Among Chinese Wine Consumersmentioning
confidence: 99%